Ответы и объяснения

Лучший Ответ!
2014-04-06T16:35:34+00:00
290) 1)  \frac{4}{a+2} - \frac{3}{a-2}+ \frac{12}{a ^{2}-4 }  = \frac{4a-8-3a-6+12}{(a-2)(a+2)} = \frac{a-2}{(a-2)(a+2)}= \frac{1}{a+2}
2) \frac{6m}{m-3}+ \frac{m ^{2}+m }{4}  * \frac{8}{m+1}= \frac{6m}{m-3}+ \frac{m(m+1)}{4}* \frac{8}{m+1}= \frac{6m}{m-3}+2m= \frac{2m ^{2} }{m-3}
291) 1) (\frac{x}{x+1}+1)* \frac{1+x}{2x-1}= \frac{2x+1}{x+1}* \frac{1+x}{2x-1}= \frac{2x+1}{2x-1}
2) ( \frac{4y}{2-y}-y): \frac{y+2}{y-2}= \frac{y ^{2}+2y }{2-y}*(- \frac{2-y}{y+2})=-y
где вы нашли?
Кого
пример (ответ на примеры)???
Сам решил
Комментарий удален